Factors Influencing the Success of Electronic Prescription Implementation in Indonesia: A Literature Review - Audry Lintang Hasanuddin; Rasmi Zakiah Oktarlina; Dwi Aulia Ramdini; Oktafany Oktafany (Jurnal EduHealth, 2025)
Electronic prescribing, or e-prescribing, is a digital system that allows doctors to create prescriptions and send them to specific pharmacy computers connected to an electronic prescription network, facilitating direct communication between physicians and their practices. Rapid technological advances in healthcare have made it easier for doctors to prescribe medications electronically, eliminating the need for handwritten prescriptions. In e-prescribing, prescriptions are sent over a secure internet network, requiring user authentication through a username and password. Benefits of implementing electronic prescribing include reducing medication errors in prescription interpretation, increasing prescription processing efficiency, and improving the quality of healthcare services. Implementing electronic prescribing often faces challenges, such as inadequate funding, negative perceptions of the technology, lack of computer skills, and complexity in data entry. This article aims to identify factors influencing the successful implementation of electronic prescribing in Indonesia. A literature review using scientific databases including Google Scholar, PubMed, and NCBI has been conducted. Various factors have been identified that can influence the effectiveness of electronic prescribing, including organizational elements, technological aspects, and human resources. Understanding these factors can guide policy development and the assessment of healthcare workers in implementing electronic prescribing, resulting in effective electronic prescribing.